Principal Risk Factors Leading to Losing Employment - Čapek, Nicholas; Fučík, Vojtěch; Janda, Karel; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2018)
This thesis concerns itself with unemployment, specifically identifying risk factors that predispose a person to become unemployed. It is done by creating a logistic regression model on bank data. Weight of evidence transformation was first applied to the predictor variables and only the most significant used in the model. Suspect factors were manually included. A decision tree model was also constructed for comparison. Findings reveal the most significant factors to be maternity and net income. Other factors include age, education, marital status and gender.
Vedoucí práce: Vojtěch Fučík
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: finance [obor bakal. práce]; bakalářské práce; bachelor's theses